TAJEN DAN PERISTILAHANNYA - I Nengah Mileh; Ida Bagus Astika Pidada (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2022)
This research is entitled â€œTajen and its terminologyâ€. Tajen as part of Balinese culture has existed and lived in Balinese society since ancient times. Tajen is usually equated with cockfighting in Bali. The sustainability of tajen cannot be separated from the terms used in tajen by gamblers. These terms are used as a medium of communication by the players, so that tajen can run well. This study aims to understand about tajen and at the same time take an inventory of the terms it uses. Observation methods and interview methods were used in data collection, synchronous descriptive methods were used in data processing, and informal methods were used to present the results of the analysis. In this study it was found that tajen is a common cockfighting in Bali. The word tajen comes from the word taji which then gets the suffix -an so that it becomes tajian. Because of the process of merger, the word tajian becomes tajen. There are four forms of terms in tajen that were found, namely terms in the form of basic words, affixed words, repeated words, and compound words.